Seed Dispersal Of Syzygium Cumini By Two Species Of Fruit Bat (Cynopterus Sphinx And Rousettus Leschenaulti) In Tamil Nadu: A Review - M. Stephen; C. Albert; Juliet Vanitharani (Revista Electronica de Veterinaria, 1970)
Seed dispersal plays a crucial role in the regeneration and survival of plant species. Syzygium cumini (commonly known as Jamun) is a significant tree species found in tropical regions of India, including Tamil Nadu. This review focuses on the seed dispersal mechanisms of Syzygium cumini by two fruit bat species, Cynopterus sphinx and Rousettus leschenaulti, which are key contributors to the plant's reproductive success. The fruit bats feed on the fleshy pulp of the Jamun fruit, and through their movements, they transport seeds over long distances, thus promoting gene flow and the establishment of new plants. By reviewing the existing literature on fruit bat-mediated seed dispersal, this article examines the role of Cynopterus sphinx and Rousettus leschenaulti in the dispersal ecology of Syzygium cumini in Tamil Nadu. The review also explores the implications of bat-mediated seed dispersal for forest regeneration, ecosystem health, and biodiversity conservation. Furthermore, the article discusses the interrelationship between fruit bats and Syzygium cumini, highlighting their role in maintaining ecological balance.